Development of durable membranes for challenging wastewater treatment via membrane distillation - Zhang, Yujun (Nanyang Technological University, 2023)
The large volume of wastewater containing a high concentration of salinity or organic solvent poses significant challenges to conventional sewage plants. In order to reduce the volume of these challenging waste streams, membrane distillation (MD) is a promising solution. As a thermal-driven process, MD utilizes the partial vapour pressure difference to separate non-volatile solutes and water. It has unique strength in treating highly concentrated solutions due to its insensibility to osmotic pressure and high rejection of all non-volatile matters, including salt and organic solvents with high boiling points. Currently, most commercial MD membranes are made of conventional hydrophobic polymers, such as polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE) and polypropylene (PP). Nevertheless, these membranes have limitations such as limited hydrophobicity (PVDF), difficulties in manufacturing (PP and PTFE), or relatively high cost (PVDF and PTFE). In order to expand the range of available MD membranes, substantial efforts have been made to obtain hydrophobic membranes from materials with limited hydrophobicity. It is usually achieved by conducting hydrophobic modification to the nascent membranes. The modified membranes have been reported with benefits such as reducing membrane cost and improving MD performance. However, these hydrophobic modification methods are often complex and expensive, impeding the large-scale use in industry, and the modified-membranes have not been examined in a challenging environment containing high concentration of pollutants. Furthermore, MD’s potential in dealing with challenging waste streams has not been fully investigated, especially for the separation of water-solvent mixtures, namely solvent resistance MD (SR-MD). To tackle these challenges, this research first aims to develop a facile, scalable and cost-effective hydrophobic modification method to tune the wettability of hydrophilic substrates to hydrophobic for the MD process. Porous commercial membranes including nitrocellulose (NC) and nylon were modified with a cost-effective fluoroethylene vinyl ether resin. The modified-NC membranes showed good hydrophobicity and outstanding performance in desalination of 3.5-10 wt% NaCl for over 120 hours. The results revealed that using a modified-hydrophilic membrane in MD is practicable and even can outperform the commercial polyvinylidene fluoride membrane. Besides, the potential of SR-MD in separating water and organic solvent with a high boiling point was comprehensively studied. Solvent-resistant porous ceramic membranes were modified by fluoroalkylsilane to acquire hydrophobicity and applied to separate 3.5-85 wt% dimethyl sulfoxide (DMSO) solution via vacuum MD. Influences of membrane pore size, membrane structure, feed temperature, and feed concentration were studied to fully understand the process. SR-MD has shown superior flux compared with the other membrane process and the modified ceramic membranes were proved to be more effective and stable in the highly concentrated DMSO solution than commercial PTFE membranes. Moreover, rejection of the SR-MD process was distinctly 105% better than the theoretical rejection estimated from vapour-liquid equilibrium at a DMSO concentration of 85 wt%. On the basis of this research, another membrane suitable for SR-MD was prepared by fatty acid chloride grafting for the first time. This new modification method used widely much cheaper and greener than the previous method and the modified membranes showed comparable SR-MD performance with the commonly silane-grafted membranes. The excellent separation performance in treating water-DMSO mixture again demonstrated the potential of SR-MD in dealing with this kind of wastewater. In summary, this thesis highlights the potential of membrane distillation for treating challenging waste streams, particularly those with high salinity or organic solvents with high boiling points. Moreover, this research also develops effective and straightforward hydrophobic modification methods, which have great potential to scale up. This work can guide the development of future MD processes for industrial applications and lead to more effective solutions for wastewater treatment.